Biomarkers and their use in occupational medicine - Aitio, Antero (Scandinavian Journal of Work, Environment & Health, 1999)
Biomarkers of exposure, parent chemicals, metabolites, and also hemoglobin and DNA (deoxyribonucleic acid) adducts, even urinary mutagenicity, have been used successfully to identify exposed persons, follow-up exposure, and quantitatively assess exposure. Some have been validated as indicators of health risk. The avenues for future biomarkers of exposure are in the development of robust, simple, and inexpensive semiquantitative methods for daily use on every worker for assuring that no (excessive) exposure takes place. Some biomarkers of effect have also been well validated and are widely used in routine monitoring activities. However, with the exception of cholinesterase inhibitors, biomarkers of effect offer little advantage over the analysis of the chemical itself. Their use will be limited to carefully planned ad hoc studies. Biomarkers of susceptibility currently have no practical application in worker health protection. Biomarker research should concentrate on validating methods, in terms of the prediction of health effects, and on elucidating exposure-biomarkers concentration relationships.
Keywords: biomonitoring; chemical hazard; exposure assessment; health surveillance